Hubungan Burnout dengan Gangguan Kualitas Tidur Pada Mahasiswa Fisioterapi Universitas Muhammadiyah Malang - Aprilia Ayu Putri; Zidni Imanurrohmah Lubis; Nurul Aini Rahmawati (Universitas Malahayati, 2026)
ABSTRACT University students commonly report burnout as a mental-health concern, and physiotherapy students face a particularly demanding version of it: thesis completion, laboratory practicum, and clinical-practice preparation all compete for their time and energy at once. When academic pressure runs high, sleep is frequently what suffers first, which can undercut both the physical and mental readiness and the academic performance of students approaching graduation. This study examined the relationship between burnout and sleep quality disturbance in the 2023 cohort of the Physiotherapy Study Program at Universitas Muhammadiyah Malang, using an analytical-observational design with a cross-sectional approach. All 106 students within the population were enrolled as the sample through total sampling. Burnout levels were measured with the School Burnout Inventory (SBI; Salmela-Aro et al. 2016), which reports a Cronbach's Alpha of 0.80 to 0.88, while sleep quality was measured with the Pittsburgh Sleep Quality Index (PSQI; Buysse et al. 1989), whose Indonesian-language version carries a reliability of 0.83. Data were checked for normal distribution with the Shapiro-Wilk test before the Pearson correlation was applied. Most respondents were female (73.6%); burnout most often fell into the above-average level (54.7%), and 93.4% of respondents reported poor sleep quality. The Pearson correlation analysis produced p = 0.000 (p 0.05) and r = 0.351, indicating a weak yet positive correlation, meaning students who reported higher burnout also tended to report poorer sleep. Burnout therefore appears to be one contributor to sleep disturbance among final-year physiotherapy students, pointing to a need for academic-workload management and psychological-support strategies capable of protecting students' readiness for both coursework and clinical practice. Keywords: School Burnout Inventory, Pittsburgh Sleep Quality Index, Academic Exhaustion, Sleep Quality. ABSTRAK Burnout menjadi salah satu keluhan kesehatan mental yang paling banyak dilaporkan mahasiswa, dan mahasiswa fisioterapi menghadapi versi yang lebih berat darinya: penyusunan skripsi, praktikum laboratorium, dan persiapan praktik klinik sama-sama memperebutkan waktu dan energi mereka. Saat tekanan akademik meningkat, tidur sering menjadi hal pertama yang terganggu, yang pada gilirannya dapat menekan kesiapan fisik dan mental serta capaian akademik mahasiswa menjelang kelulusan. Penelitian ini menguji hubungan antara burnout dan gangguan kualitas tidur pada mahasiswa angkatan 2023 Program Studi Fisioterapi Universitas Muhammadiyah Malang, memakai desain observasional analitik berpendekatan cross-sectional. Seluruh 106 mahasiswa dalam populasi diikutsertakan sebagai sampel lewat teknik total sampling. Tingkat burnout diukur memakai School Burnout Inventory (SBI; Salmela-Aro et al. (2016) yang memiliki Cronbach's Alpha 0,80–0,88, sedangkan kualitas tidur diukur memakai Pittsburgh Sleep Quality Index (PSQI; Buysse et al. (1989; Salmela-Aro et al., 2016) yang versi Bahasa Indonesianya memiliki reliabilitas 0,83. Data lebih dulu diuji normalitasnya dengan Shapiro-Wilk sebelum dianalisis memakai korelasi Pearson. Mayoritas responden berjenis kelamin perempuan (73,6%); tingkat burnout paling banyak berada pada tingkat di atas rata-rata (54,7%), dan 93,4% responden melaporkan kualitas tidur yang buruk. Analisis korelasi Pearson menghasilkan p = 0,000 (p 0,05) dan r = 0,351, menandakan hubungan positif namun lemah — mahasiswa yang melaporkan burnout lebih tinggi juga cenderung melaporkan tidur yang lebih buruk. Dengan demikian, burnout tampak menjadi salah satu faktor di balik gangguan tidur pada mahasiswa fisioterapi tingkat akhir, yang mengarah pada perlunya strategi manajemen beban akademik dan dukungan psikologis untuk menjaga kesiapan mahasiswa, baik dalam perkuliahan maupun praktik klinik. Kata Kunci: School Burnout Inventory, Pittsburgh Sleep Quality Index, Kelelahan Akademik, Sleep Quality.